Investigating The Role of Servant Leadership in Driving Job Performance and Fostering Employee Engagement: A Comprehensive Study - Deepak Kumar; Prof. (Dr) Rajni Saluja (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This study explores the impact of servant leadership on employee engagement, growth, and job performance within the IT industry across 24 districts in India. Employing a mixed-methods research design, the study integrates both quantitative and qualitative approaches to provide a holistic understanding of the measurable effects and nuanced experiences of employees under servant leadership. A sample size of 460 participants, determined using G Power software, ensures robust statistical analysis while accommodating potential dropouts. A multistage sampling technique is used, beginning with the selection of 24 advertising companies from Haryana, Uttar Pradesh, Rajasthan, and Delhi/NCR through pro-purposive sampling, followed by a random selection of 460 employees evenly distributed by gender and stratified by age and income profiles. The study's structured sampling framework ensures comprehensive representation, with respondents distributed across regions to reflect the diversity of the advertising industry. Participants include 112 employees each from Haryana, Uttar Pradesh, and Rajasthan, and 124 from Delhi/NCR, ensuring balanced representation of male and female employees. This approach allows the study to capture servant leadership's impact across various demographic segments and organizational contexts. By examining both statistical data and qualitative insights, the research provides a deeper understanding of how servant leadership fosters employee engagement, enhances job performance, and contributes to organizational success within the advertising sector.